PENGARUH LABA KOTOR, LABA OPERASI, DAN LABA BERSIH DALAM MEMPREDIKSI ARUS KAS DI MASA MENDATANG (Studi Empiris Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - Ningsih, Suhesti; Utami, Wikan Budi; Hidayatullah, Andifa Rozaq; Novianti, Laras Dwi (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze gross profit, operating profit and net profit in predicting future cash flows in manufacturing companies in the consumer goods industry sector listed on the IDX for the 2018-2020 period. Sampling using purposive sampling with time series data in order to obtain a sample of 84. The data method in this study used descriptive statistics test, classical assumption test and hypothesis testing with F test, t test and R test. F test results obtained a significance value of 0, 00 < 0.05 then the model is feasible to use, this means that all independent variables have an effect on the dependent variable. From the results of the hypothesis test, namely the t test, it shows that the gross profit variable has an effect on predicting cash flows, this is evidenced by the significance value of 0.00 < 0.05. The operating profit and net income variables have a significance value greater than 0.05, namely 0.425 and 0.60, thus it can be concluded that operating income and net income have no effect in predicting future cash flows. From the results of the R test, the adjusted R square value is 0.426 or 42.6%. This shows that the variables of gross profit, operating profit, and net profit simultaneously have an effect on predicting future cash flows by 42.6%. While the remaining 58.4% is influenced by other factors outside the study.